El sector cooperativo: un medio para hacer de las remesas de trabajadores un recurso productivo (2006)
The remittances of the workers living in foreign countries in the last years have become important income for their countries of origin. From recent information we know as a fact than the remittances nowadays represent and important percentage of GIP (Gross Internal Product), particularly in Latin-American countries; there are several reasons why this subject has become of considerable importance, since these resources are contributing to the economic development of these countries if there are use properly and especially for productive purposes. From the considerations mentioned above, emerges an important question: ¿How to make these resources more productive in order to have an effect in the economic growth? In Colombia there is considerable interest to move forward to answer this question, particularly Banks and financial institutions. Nevertheless we believe that the creation an appropriate environment and organization in order to canalize an efficient cooperative system to strength the productive system and to activate economical growth.